C programming in easy steps - McGrath, Mike, 1956- (Leamington Spa : In Easy Steps, 2012)
The C programming language is taught in every foundation IT course in the UK. This guide covers the subject in a non-technical style ideal for beginners.
Previous ed.: 2009.
Text on inside cover.
Includes index.
Keywords: C (Computer program language); Digital Lifestyle